Pathogenicity of Aeromonas hydrophila in high-value native Pangasius catfish, Pangasius nasutus (Bleeker) - Sani, Bashir; Yusoff, Md. Sabri; Md Yasin, Ina Salwany; Abd Karim, Murni Marlina; Matori, Mohd Fuad; Amal, Mohammad Noor Azmai; Manchanayake, Tilusha; Zahaludin, Amir-Danial; Mohamad, Aslah (Universiti Putra Malaysia Press, 2023)
Pangasius catfish, Pangasius nasutus, is a promising candidate for aquaculture due to its high market value. However, the presence of pathogenic bacteria in Aeromonas hydrophila is a major concern in P. nasutus farming in this country. This study determines the pathogenicity of A. hydrophila in P. nasutus. A total of 80 P. nasutus juveniles were intraperitoneally injected with 0, 103 , 105 , and 107 CFU mL-1 of A. hydrophila and monitored until 240 hr. The infected moribund fish’s kidneys, livers, and spleens were collected for histopathological analysis. The LD50-240hr value was found at 0.8 × 104 CFU/ml of A. hydrophila. The percentage of mortality in 0, 103 , 105 , and 107 CFU/ml infected groups were found to be at 0, 40, 60, and 90, respectively. The infected fish showed congestion at the base of the fin, ascites, enlarged gall bladder, and swollen spleen. It is the earliest report on A. hydrophila’s pathogenicity in high-value native fish, P. nasutus.